Representation of Indonesian women workers: a critical discourse analysis on the newspapers of nationalist-secular and Islamic ideological perspectives - Badara, Aris; Jamiludin, Jamiludin (Indonesian Journal of Islam and Muslim Societies, 2020)
The purpose of this study is to reveal the representation of women workers in newspaper news discourse that follows the nationalist-secular ideology and the Islamic ideology perspectives. The method of this research is a qualitative content analysis that views the text as a symbolic message and it requires interpretation according to the context. Complementing the research method, a critical discourse analysis approach is also used. The subjects of this research are female workers found in newspaper news discourse that carries the values of Islamic ideology and newspapers that carry nationalist-secular ideology. Data were analyzed through critical discourse analysis techniques in the following steps: (a) description; (b) interpretation; and (c) explanation. This research still considers checking the reliability and the validity. Data analysis is also complemented by confirmation of linguists and peers (triangulation of sources). The main findings of this study show that the practice of discourse in the RM newspaper which follows the nationalist-secular ideology perspective represents marginal women. By the RM newspaper, the representation is used as a plea for the actions and trait of male actors or employers. The motive revealed from this phenomenon is to follow the demand of the market. On the other hand, the newspaper R, which tends to follow Islamic ideology perspective, represents the motive of advocacy for women workers. This is the implication of the values of Islamic ideology carried out by the R newspaper as mentioned in its vision and mission. The findings are also the antithesis of the view that Islam isolates women in the social sphere of society.